State liability and the enforcement of arbitral awards infringing EU law, a zero-sum game after Tomášová? - Moreiro González, Carlos J. (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The CJEU doctrine regarding to commercial arbitration addresses several aspects of the complex relationships between arbitration and EU Law. Nonetheless, since there is no established regulatory standard, the national court’s review of the conformity of arbitration awards with the EU legal order is conducted according to different criteria. As national courts are faced with obligations of varying degrees, there is the risk of detaching themselves from the obligation to protect this legal order, with a corresponding impact on the creation of situations that could give rise to State liability for infringements of EU Law. Although in its judgment in the Tomášová case the CJEU recognizes very restrictive grounds for the liability of a Member State in such circumstances, this does not exclude that such liability could beincurred under less restrictive circumstances either on the basis of internal law or international law.